Landslide risks along major roads heading to UiTM Pahang / Mohd Fairuz Bachok ... [et al.] - Bachok, Mohd Fairuz; Zainudin, Mohd Razmi; Wan Abdullah, Wan Zukri; Mohd Saim, Noraida; Alias, Rohaya (2011)
Series on landslide that had taken placed along major roads heading to UiTM Pahang namely Jerantut to UiTM Pahang road, Maran to UiTM Pahang road and Temerloh to UiTM Pahang road indicates that slopes alongside those particular roads have a potential of landslide occurrence. This is due that alongside those roads have many slopes. Landslide is one of the natural disasters in Malaysia and commonly occurred during rainy season. Landslide will pose serious threats such as damages of properties, claim life and injuries and delays development planning. In Malaysia, most of the landslides have occurred on cut slopes or on embankments alongside roads and highways in mountainous areas. When a landslide occurred at any location along the road, it does not only block the road and cut off the connection from one place to another but also might cause the risk of injury or death for those using the road Thus, this study is carried out to identify slopes that prone of landslide occurrence, so that UiTM Pahang staff should take further action and precaution every time they are travelling near to risk slopes at those particular roads. Beside than highlighted information of landslide risk early warning, this study also will highlight which of those roads should be given a priority in preventive measures. Therefore, it is hopes that this study could become and initial example for preventive action of staff safety not only for UiTM Pahang but also for others UiTM campuses especially that are constructed on uneven terrain.